Protective effect of gastrodin on peripheral neuropathy induced by anti-tumor treatment with vincristine in rat models. (2nd January 2021) - Qin, Bingjie; Luo, Ni; Li, Yuxing; Gong, Denghui; Zheng, Jun; Tan, Xiao; Zheng, Weihong
Abstract: Cancer is a common disease threatening human health, chemotherapy is widely used in clinical treatment of cancer, but chemotherapy-induced peripheral neuropathy (CIPN) has a relevant impact on life quality of cancer patients. Administration of gastrodin can relieve chronic pain to cancer patients with CIPN and attenuated the inflammatory response by reducing the expression of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6). However, its exact molecular mechanisms remain unclear. In this study, we established an animal model of CIPN using Walker-256 breast cancer cell and vincristine. We found that the mechanical and thermal pain threshold of rats was decreased with treatment of vincristine. Using gastrodin could restore the mechanical and thermal threshold without interfering anti-tumor effect of vincristine. Gastrodin relieved CIPN by inhibiting activation of spinal microglia through Fractalkine (CX3CL1) and its receptor CX3CR1, then inhibited P38/mitogen-activated protein kinase (MAPK) signaling pathway and reduced the expression of inflammatory factor TNF-α and interleukin-1β (IL-1β). Taking together, our study demonstrated that gastrodin is a potential drug for the treatment of CIPN and likely to improve cancer patient's life quality.